2021
DOI: 10.2147/amep.s315041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peer-Assisted Learning on Enhancing Clinical Research Skills Among Medical Students: Students’ and Tutors’ Perceptions

Abstract: Purpose Research methodology is an essential part of evidence-based medicine. Many educational programs include clinical research methodology within their curriculum. Moreover, students’ preferences for learning methods are different than before, as they now prefer alternative methods, such as peer teaching. Peer-assisted learning enhances students’ tutoring skills. Thus, the current study aimed to evaluate the effect of peer teaching on enhancing clinical research skills. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Perceived barriers to implementing an anesthesia PWP included concerns regarding poor peer engagement and poor resource quality. However, in contrast, Jawhari et al [ 37 ] found that the top barriers to PAL in Saudi Arabia included taking more time than traditional teaching and peers having insufficient knowledge to teach. Very few people reported time concerns in our study, which may reflect differences in teaching methods in various countries.…”
Section: Discussionmentioning
confidence: 98%
“…Perceived barriers to implementing an anesthesia PWP included concerns regarding poor peer engagement and poor resource quality. However, in contrast, Jawhari et al [ 37 ] found that the top barriers to PAL in Saudi Arabia included taking more time than traditional teaching and peers having insufficient knowledge to teach. Very few people reported time concerns in our study, which may reflect differences in teaching methods in various countries.…”
Section: Discussionmentioning
confidence: 98%
“…Tutors are recognized for providing accurate and focused guidance, meeting the needs of non-tutoring students (Jawhari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Peer teaching has been widely studied and adopted in higher education across many disciplines in instructional venues such as labs, clinical settings, course sections, and discussion groups (for example, Brueckner and MacPherson, 2004;Khaw and Raw, 2016;Burgess et al, 2020). Overall, the literature finds an educational benefit not only to the peer teacher but also the students being taught by peers, or at least a comparable, not diminished, learning by students (Whitman and Fife, 1988;Wagner and Gansemer-Topf, 2005;Secomb, 2008;Rees et al, 2016;Jawhari et al, 2021). While peer learning in libraries has been adopted through peer reference and teaching assistants (MacAdam and Nichols, 1988;Murphy, 2016;Baugess et al, 2017;Salomon et al, 2017), solo peer teaching, especially undergraduate-to-undergraduate, has not been as widely explored or deployed in academic libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, the literature finds an educational benefit not only to the peer teacher but also the students being taught by peers, or at least a comparable, not diminished, learning by students (Whitman and Fife, 1988; Wagner and Gansemer-Topf, 2005; Secomb, 2008; Rees et al. , 2016; Jawhari et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%